Exploring the personal benefits of surfing: insights from cold-water surfers in Jæren, Norway - Elmahdy, Yasmine M.; Orams, Mark; Mykletun, Reidar J. (Frontiers in Sustainable Tourism, 2024)
Introduction Surfing has grown since the 1960s to become a global marine leisure activity. Traditionally, surfing is associated with tropical and temperate climates and a sea, sand, and sun setting. However, surfing's geographical spread now includes polar and sub-polar regions, areas where the cold and sea-conditions provide challenges to human survival. Methods This study uses a phenomenological approach to identify and explore the personal benefits gained by experienced surfers in the Jæren region, south of the city of Stavanger in Norway. Data were obtained from semi-structured in-depth interviews with 13 experienced surfers who surf year-round, but primarily in winter, in extreme conditions. Additional secondary data were derived from written and video material published in online surfing blogs/vlogs and surfers' private video footage. Results and discussion Participants gained a wide range of benefits including experiencing strong positive feelings, inclusion, and social cohesion with other members in the surfing subculture, a deep connection to nature, physical and mental health benefits, and an overall enhanced quality of life. While international surf travel was constrained by the COVID-19 pandemic, local surfing was reinforced. This resulted in surfing becoming an opportunity to safely socialize with others outside of one's family, thus increasing the social benefits of the sport. This study presents the first empirical data on the personal benefits of surfing from a non-traditional cold-water surfing nation in Scandinavia.